Report of the Healthy Survey and Development Committee Vol. IV Summary - Planning Commission (Planning Commission, 1946)
Our survey of existing health conditions in India in volume 1 of the report extends to about 220 pages, while the recommendations for the creation of a better standard of national health through the development of an organised health service on modern lines are embodied in a second volume of over‘500 pages. In these two volumes we have dealt, at some length, with India's health problems in order to present an adequate picture of the existing state of affairs and of the proposals for its improvement. In addition to such detailed consideration of matters relating to India’s present and future health administration we feel that it may be of advantage to give, in a much smaller compass, the salient -features of our report in the present volume. In this summary we have not strictly adhered to the chronological order of the chapters in the first two volumes of our report. It deals with different subjects such as personal health services, environmental hygiene, professional education, medical research and so on in separate sections and indicates briefly, in each section, the more important matters relating to the subject concerned in respect of both the existing conditions and of our proposals for their improvement. In presenting a picture of health conditions in India we have confined ourselves to the period ending with 1941 in order to exclude the adverse effects of abnormal conditions arising out of the War, particularly after Japan’s entry towards the end of that year. The present state of the public health in British India is low as is evidenced by the wide prevalence of disease and the consequent high rates of mortality in the community as a whole and, in particular, among such vulnerable groups as children and women in the reproductive age period. The death rate for the general population in British India was, in 1937, 22-4 per 1,000 inhabitants and for infants (children under one year of age) 162 per 1,000 live births. In 1941 the corresponding rates were 21-8 and 158 respectively.
Summary
Government of India New Delhi